2001
DOI: 10.1027//0269-8803.15.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Heart Rate and the Severity of Motion Sickness Caused by Optokinetic Stimulation

Abstract: Heart rate has been reported to increase during nausea and has therefore been used as an indicator of motion sickness. However, the relationship between heart rate and subjective ratings of motion sickness has received little attention, and the autonomic origins of any increase in heart rate during motion sickness are unknown. Spectral analysis of heart rate variability can quantify the degree of sympathetic and parasympathetic stimulation of the heart, as reflected by the low frequency (LF) power and high fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 12 publications
5
34
1
Order By: Relevance
“…Results of this study showed that HRVs derived from the recorded ECG signals during low-MS level period differed from the ones during high-MS level period for most of the subjects, consistent with previous HRV studies noted that exposure to motion sickness stimulation would increase cardiac sympathetic while decrease cardiac parasympathetic activities [4,6,13]. However, one subject (atypical) had autonomic responses opposite to those of the majority of the subjects (n=4) during MS exposure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of this study showed that HRVs derived from the recorded ECG signals during low-MS level period differed from the ones during high-MS level period for most of the subjects, consistent with previous HRV studies noted that exposure to motion sickness stimulation would increase cardiac sympathetic while decrease cardiac parasympathetic activities [4,6,13]. However, one subject (atypical) had autonomic responses opposite to those of the majority of the subjects (n=4) during MS exposure.…”
Section: Discussionsupporting
confidence: 86%
“…After finishing the experiment, each subject was required to fill a MS questionnaire [13] to recall the levels of MS during the experiment. In the questionnaire, the subjects used 6 levels (0 -5) to report their symptoms of MS (with 0=no MS, 1=stomach awareness, 2=stomach discomfort, 3=slight nausea, 4=moderate, 5=severe nausea).…”
Section: B Experimental Setupmentioning
confidence: 99%
“…galvanic skin responses (GSR) [6], and heart rate variability (HRV) [7]. In addition, electroencephalography (EEG) has been employed by many studies as an effective motion-sickness index due to its high temporal resolution and portability [2].…”
mentioning
confidence: 99%
“…Ataxia in simulator-induced sickness has been reported. The influence of videoinduced motion sickness on the body has been measured employing subjective scales, such as the Simulator Sickness Questionnaire (SSQ) [7], and by quantitatively investigating the relationship between external factors and internal conditions using physiological indices [8][9][10][11], such as respiratory function, electrocardiogram, skin electrical activity, fluctuation of the center of gravity, and electrogastrogram.…”
Section: Introductionmentioning
confidence: 99%